Susceptibility to frequent exacerbation in COPD patients: Impact of the exacerbations history, vaccinations and comorbidities?. (August 2020) - Ouaalaya, El Hassane; Falque, Laurent; Dupis, Jean Michel; Sabatini, Marielle; Bernady, Alain; Nguyen, Laurent; Ozier, Annaig; Nocent-Ejnaini, Cécilia; Le Guillou, Frédéric; Molimard, Mathieu; Zysman, Maéva; Raherison-Semjen, Chantal
Abstract: Introduction: Exacerbations are key events in the natural history of COPD, but our understanding of their longitudinal determinants remains unclear. We used data from a large observational study to test the hypothesis that vaccination status and comorbidities could be associated with the occurrence of exacerbations profile. Methods: Diagnosed COPD patients have been included by their pulmonologists, with up to 3 years of follow-up. Data were analyzed using the KmL method designed to cluster longitudinal data and receiver operating characteristic curve analysis to determine the best threshold to allocate patients to identified clusters. Results: 932 COPD patients were included since January 2014, 446 patients (65.68% males, 35.59% current smokers) were followed over a period of 3 years with complete data. 239(28.15%) patients reported two or more exacerbations in the year before enrolment (frequent exacerbations). Among them 142(16.68%) also had frequent exacerbations in the first year of the study, and 69(8.10%) who remained frequent exacerbators in the second year. Based on our hypothesis, we were able to determine four phenotypes: A (infrequent), B (frequent in underweight patients), C (transient), and D (frequent in obese patients). Frequent exacerbators had more airflow limitation and symptoms. Irrespective of cut-offs set to define the optimal number of clusters, a history of exacerbations OR: 3.72[2.53–5.49], presence of anxiety OR: 2.03[1.24–3.31] and absence of the annual influenza vaccination OR: 1.97[1.20–3.24] remained associated with the frequent exacerbator phenotypes. Conclusions: The most important determinants of frequent exacerbations are a history of exacerbations, anxiety and unvaccinated against influenza. Highlights: Four phenotypes: A (infrequent), C (transient), B (frequent exacerbations in underweight patients) and D (frequent exacerbations in obese patients). The confirmation of the current used threshold of two exacerbations per year to identify the frequent exacerbator phenotype. Unvaccinated against influenza, history of exacerbations and anxiety are the most important determinants of this phenotype.